Triadic Scaffolds: Tools for Teaching English Language Learners with Computers - Carla Meskill (Language Learning and Technology)
Active communication with others is key to human learning. This straightforward premise currently undergirds much theory and research in student learning in general, and in second language and literacy learning in particular. Both of these academic areas have long acknowledged communication's central role in successful learning with the exact intricacies of instructional conversations and the forms these take having been the focus of close analysis (Cazden, 1988; Gee, 2001; Nystrand, Gamoran, Kachur, & Prendergast, 1997; Tharp & Galimore, 1991; van Lier, 2000). In this examination of computer-supported classroom discourse, specific forms of instructional conversation employed by a veteran elementary teacher of beginning-level English language learners (ELLs) are examined. The focal teacher orchestrates instructional conversations around computers with children whose immediate needs are to learn the English language, specifically the "language of school" and the concomitant social complexities implied in order to participate in mainstream instructional activity. With these goals shaping language and literacy activity, their ESOL (English for speakers of other languages) teacher makes use of the computer to capture, motivate, and anchor learner attention to, and render comprehensible the target language they hear and see on and around the computer screen. The anatomy of the activity she orchestrates around the computer and the language she uses to support it -- labeled here as triadic scaffolds -- are the focus of analysis. Forms and functions of triadic discourse (teacher, learner, computer) are examined for their potential unique role in second language and literacy instruction.